Fine particulate matter air pollution and the mortality of children under five: a multilevel analysis of the Ethiopian Demographic and Health Survey of 2016 - Shiferaw, Ashenafie Bereded; Kumie, Abera; Tefera, Worku (Frontiers in Public Health, 2023)
Background: Every year, polluted air is costing the globe 543, 000 under-five children deaths. The particulate matter below 2.5 m diameter (PM2.5) is a part of air pollution that has adverse effects on children’s health. In Ethiopia, the effect of ambient PM2.5 is least explored. This study aimed to assess the association between PM2.5 and under-five mortality in Ethiopia. Methods: The study used the data from Ethiopian Demographic Health Surveys conducted in 2016, collected between January 18 and June 27. Under-five children with the child mortality information and coordinates of geographical location were included. Exposure to ambient PM2.5 concentration was a satellite-based estimate by the Atmospheric Composition Analysis Group at Washington and Dalhousie University, in the United States and Canada, respectively. Annual mean pollution level and mortality datasets were matched by children’s geographical location and dates of birth, death, and interview. The relationship between ambient PM2.5 and under-five mortality was determined by multilevel multivariable logistic regression on R software. The statistical analyses were two-sided at 95% confidence interval. Results: The study addressed 10452 children with the proportion of under-five mortality being 5.4% (95% CI 5.0% – 6.8%). The estimated lifetime annual mean exposure of ambient total PM2.5 was 20.1 3.3 gm-3. A ten-unit increase in lifetime annual mean ambient total PM2.5 was associated with 2.29 [95% CI 1.44 – 3.65] times more odds of under-five mortality after adjusting for other variables. Conclusions: Under-five children are exposed to higher levels of ambient PM2.5 concentration exceeding the limit set by the World Health Organization. Ambient PM2.5 is significantly associated with under-five mortality adjusted for other variables. Strong measures need to be taken to reduce air pollution.